Comparative study of the skin pathergy test with blunt and sharp needles in Behçet's disease: confirmed specificity but decreased sensitivity with sharp needles. Issue 11 (November 1993) - Dilşen, N; Koniçe, M; Aral, O; Ocal, L; Inanç, M; Gül, A
Abstract : OBJECTIVE–To compare the specificity and sensitivity of the skin pathergy test performed with blunt and sharp needles in patients with Behçet's disease. METHODS–The skin pathergy test was performed using the simultaneous four needle prick method with blunt and sharp, thick and thin needles in 92 patients with Behçet's disease, 64 healthy controls, and 128 patients without Behçet's disease. The test was evaluated at 48 hours. RESULTS–No positive skin pathergy test was found in healthy controls and patients without Behçet's disease. The frequency and intensity of the positive skin pathergy test with blunt needles were significantly higher than those with sharp needles. CONCLUSION–This study reconfirmed the specificity of a positive skin pathergy test for Behçet's disease using blunt and sharp needles and showed a decreased sensitivity and intensity of the reaction with sharp needles.